PERCEPTION OF PATIENTS REGARDING THE FACTORS THAT INFLUENCE THE SAFETY OF THE MEDICAL ACT - Balcoș Carina; Bamboi Irina; Hurjui Loredana; Feier Ramona; Anca Rapis; Roșu Leata Gabriela; Nicolau Andrei; Romanec Cristian; Armencia Adina (Romanian Dental Association for Education, 2023)
The medical care sector is viewed as having a high level of risk, and the provision of health services is considered particularly dangerous. Aim: The purpose of this study was to evaluate how patients perceive the elements that contribute to accessing quality medical services. Material and methods: To assess the attitude and knowledge of the population regarding infection control in dental clinics, we initiated a questionnaire-based study with 25 questions involving 75 patients who presented for dental treatments at two private clinics in Iași. The response rate was 96%. Results: 27% of patients discussed with the dentist about the risk of illness through blood-borne diseases during dental treatments. 65.5% of the subjects affirm that a dentist infected with HIV can provide dental treatments under the conditions of using protective equipment. All consider gloves, masks, and caps to be indispensable for the doctor when providing treatment. 87.6% of them consider that the nurse can be involved in the transmission of diseases.The main practices considered important by patients in preventing illness are the sterilization of instruments (100%) and the doctor washing their hands (86.2%), and to a lesser extent, waste handling (47.5%) and surface disinfection (100%). Conclusion: Patients have a relatively good perception regarding the factors that can influence the safety of the medical act in dental practice. The medical team has the responsibility to inform the patient in order to reduce the risk of unpleasant events occurring in the dental office.